2007
DOI: 10.1080/10691898.2007.11889549
|View full text |Cite
|
Sign up to set email alerts
|

Student and Professor Gender Effects in Introductory Business Statistics

Abstract: Studies have yielded highly mixed results as to differences in male and female student performance in statistics courses; the role that professors play in these differences is even less clear. In this paper, we consider the impact of professor and student gender on student performance in an introductory business statistics course taught by economics faculty. Using a sample of 535 students, we find, after controlling for academic and mathematical background, that students taught by a professor of the opposite g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Researchers have also investigated whether instructor gender impacts the relative performance of male versus female students with conflicting results. In a business statistics class, students with the same gender as their instructor performed significantly better than students of the opposite gender (Haley et al, 2007). Hoffmann and Oreopoulos (2009) looked at the interaction between student gender and instructor gender and its effect on course grades at the University of Toronto.…”
Section: Performancementioning
confidence: 99%
“…Researchers have also investigated whether instructor gender impacts the relative performance of male versus female students with conflicting results. In a business statistics class, students with the same gender as their instructor performed significantly better than students of the opposite gender (Haley et al, 2007). Hoffmann and Oreopoulos (2009) looked at the interaction between student gender and instructor gender and its effect on course grades at the University of Toronto.…”
Section: Performancementioning
confidence: 99%
“…In STEM courses, females participated more and identified more with the subject matter when instructors were female ( Stout et al ., 2011 ; Young et al ., 2013 ). Some studies have found that instructors of the same gender, particularly instructors students perceive as competent, can improve the performance of female students ( Haley et al ., 2007 ; Hoffman and Oreopoulos, 2009 ; Carrell et al ., 2010 ; Antecol et al ., 2012 ), while other studies found no difference ( Griffith, 2010 ; Price, 2010 ; Stout et al ., 2011 ). Thus, an instructor effect in college-level STEM courses remains a contentious issue that would benefit from further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…In each case, the male students displayed higher positive scores in all four attitudinal categories. The effect of gender on achievement in introductory statistics classes has been reviewed with variable results (Scheaffer and Stasny 2004;Alldredge and Brown 2006;Haley, Johnson, and Kuennen 2007). While a study of gender differences in introductory business statistics showed females tend to achieve higher scores than male students (Johnson and Kuennen 2006), and that students taught by a professor of the same gender do significantly better, these results do not address the attitudinal or confidence differences between genders.…”
Section: Introductionmentioning
confidence: 99%